Chief executive officer shareholding and company performance of Malaysian publicly listed companies / Heng Soo Eng, Ong Tze San and Teh Boon Heng - Heng, Soo Eng; Ong, Tze San; Teh, Boon Heng (Faculty of Accountancy, 2016)
This study aims to investigate the relationship between chief executive officer (CEO) shareholding and company performance. Specifically, the study investigates the influence of the level of direct and indirect CEO shareholdings on the market growth, profitability and liquidity of companies. A sample comprising 59 companies was obtained from Bursa Malaysia within a five-year period from 2009 to 2013. Results reveal that most CEOs of Malaysian listed companies own company shares either directly or indirectly. The CEOs of listed companies in Malaysia tend to retain controlling stakes by possessing a significant amount of shares in their companies. As a result, these companies demonstrate improved financial performance.